Hydrogeochemistry and water quality assessment in two dolomite karst springs: a case study from the Shibing dolomite karst, Guizhou plateau - Jinglin, Mo; Xiaoxi, Lyu; Shulin, Jiao; Jianghu, He; Dongnan, Wang; Chenyi, Zhu; Chenpeng, Hu; Renkai, Zhang (Frontiers in Water, 2025)
Dolomite, as a typical carbonate rock, exhibits a dual-porosity and fracture medium structure, which provides buffering systems for hydrogeochemical processes while forming unique material migration pathways. To reveal the chemical evolution patterns of karst spring water, this study collected long-term main ion chemical characteristics of karst spring water and comprehensively applied methods such as the Piper trilinear diagram, Gibbs model, ion ratios, and factor analysis to identify hydrochemical evolution characteristics and influencing factors in the spring catchment. The entropy-weighted water quality index (EWQI) was used for water quality assessment, and the potential risks of NO3-N were evaluated using the human health risk assessment (HHRA) model. The results showed: (1) The spring water in the study area is dominated by HCO3− and Ca2+, primarily derived from dolomite dissolution, with a hydrochemical type of HCO3-Ca·Mg. (2) The hydrochemical evolution in the study area is jointly influenced by rock weathering, cation exchange, and human activities, where Na+ and Cl− exhibit multi-source characteristics, mainly from atmospheric deposition and anthropogenic activities. (3) According to the Chinese “Groundwater Quality Standard” (GB/T 14848-2017), all spring water in the study area falls within the “good to excellent” category. Additionally, Pearson correlation analysis between EWQI and selected indicators revealed that Ca2+, NO3-N, and Cl− are key factors controlling water quality. Health risk assessment indicated low non-carcinogenic risks for adults (male and female) and children, with adult males showing higher risks than children and adult females. This study holds significant implications for understanding hydrochemical evolution in dolomite karst areas and ensuring national water resource security and coordinated ecological-economic development in Southwest China.